CHESTER BARNARD’S FUNCTIONS OF THE EXECUTIVE IN THE 21ST CENTURY A CRITICAL REVIEW - Khan, Huma; Singh, Nirmal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Almost a century has passed since Chester Barnard published his seminal work on Organisational Behaviour in 1938. Since then, the book has garnered criticism as well as adoration. However, the applicability of Barnard’s functions needs to be evaluated in the context of 21st century and it remains to be seen how much the core beliefs of the theory have mutated given the time that has lapsed since the work was first published.